Planning for successful participant recruitment and retention in trials of behavioural interventions: Feasibility randomised controlled trial of the Wrapped intervention. - Lauren Schumacher; Rik Crutzen; Kayleigh Kwah; Katherine Brown; Julia V Bailey; Stephen Bremner; Louise J Jackson; Katie Newby (PLOS Digital Health)
Randomised controlled trials (RCTs) must have sufficient power if planned analyses are to be performed and strong conclusions drawn. A prerequisite of this is successful participant recruitment and retention. Designing a comprehensive plan for participant recruitment and retention prior to trial commencement is recommended, but evidence concerning successful strategies, and how to go about developing a comprehensive plan, is lacking. This paper reports on the application of a six-stage process to develop a recruitment and retention strategy for a future RCT. Stage 1) Rapid evidence review: strategies used in previous trials were identified through database searching. This informed Stage 2) PPI workshop: workshops with public and patient involvement (PPI) group were used to select a sub-set of these strategies based on their potential to be successful and acceptable with the target audience. Stage 3) Focus groups with the target audience: the sub-set was refined through feedback from 15 young people (data subjected to content analysis). Strategies the PPI and focus groups mutually agreed upon proceeded directly to Stage 5; those without consensus proceeded to Stage 4. Stage 4) PPI workshop: PPI members voted on the remaining strategies; those without consensus were discarded. Stage 5) Observation of strategies during feasibility RCT (fRCT): the retained set of strategies were observed in practice in a fRCT in which recruitment and retention data and qualitative feedback from participants was collected. Stage 6) PPI workshop: the fRCT findings were reviewed and strategies for use in the future RCT were finalised. The finalised strategy included set of adverts; schedule of financial incentives; instructions to send survey invite by email, one prompt by SMS prior to data collection, and up to three SMS reminders; procedure to keep participants engaged (e.g., newsletters, personalisation of communications); and procedure if participants fail to complete a research activity (follow-up email/phone call).